The Effect of Content Marketing on Purchase Intention Mediated by E-Wom (Empirical Study: Ice Cream Consumers on Klik Indomaret) - Jackson, Jackson; Andreas , Andreas (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to analyze the effect of content marketing on purchase intention. The benefit of this study is to find out what factors influence purchase intention because it is important for ice cream manufacturers to develop online sales market share. This research method is a quantitative research method with survey methods, which is a research method to examine certain types of content by collecting primary water through the use of research instruments that are structured and systematical with the aim of testing hypotheses that have been studied. There is a positive relationship between eWOM and consumers and businesses. The formation of eWOM is the result of the company's performance in Maisai Lailu and encourages company performance in the future. eWOM is an important source of acquisition through various digital markets so that eWOM has the ability to achieve consumer acquisition, consumer retention and consumer acquisition'. Based on the results of research and discussions that have been carried out, the conclusions that can be drawn are as follows: Content marketing has a significant positive effect on purchase intention in consumers of Klik Indomaret ice cream received Content marketing has a significant positive effect on e-wom in consumers of Klik Indomaret ice cream received. E-wom has a significant positive effect on purchase intention in consumers of Klik Indomaret ice cream received. E-wom mediates the effect of content marketing on purcahase intention in consumers of Klik Indomaret ice cream received